Pharmacokinetic comparison of different flubendazole formulations in pigs: A further contribution to its development as a macrofilaricide molecule. Issue 3 (December 2015) - Ceballos, L.; Alvarez, L.; Mackenzie, C.; Geary, T.; Lanusse, C.
Abstract: Despite the well established ivermectin activity against microfilaria, the success of human filariasis control programmes requires the use of a macrofilaricide compound. Different in vivo trials suggest that flubendazole (FLBZ), an anthelmintic benzimidazole compound, is a highly efficacious and potent macrofilaricide. However, since serious injection site reactions were reported in humans after the subcutaneous FLBZ administration, the search for alternative pharmaceutical strategies to improve the systemic availability of FLBZ has acquired special relevance both in human and veterinary medicine. The goal of the current experimental work was to compare the pharmacokinetic plasma behavior of FLBZ, and its metabolites, formulated as either an aqueous hydroxypropyl- β -cyclodextrin-solution (HPBCD), an aqueous carboxymethyl cellulose-suspension (CMC) or a Tween 80-based formulation, in pigs. Animals were allocated into three groups and treated (2 mg/kg) with FLBZ formulated as either a HPBCD-solution (oral), CMC-suspension (oral) or Tween 80-based formulation (subcutaneous). Only trace amounts of FLBZ parent drug and its reduced metabolite were measured after administration of the different FLBZ formulations in pigs. The hydrolyzed FLBZ (H-FLBZ) metabolite was the main analyte recovered in the bloodstream in pigs treated with the three experimental FLBZ formulations. The oral administration of the HPBCD-solution accounted for significantly higher (P < 0.05) Cmax and AUC (23.1 ± 4.4 μg h/mL) values for the main metabolite (H-FLBZ), compared with those observed for the oral CMC-suspension (AUC = 3.5 ± 1.0 μg h/mL) and injectable Tween 80-based formulation (AUC: 7.5 ± 1.7 μg h/mL). The oral administration of the HPBCD-solution significantly improved the poor absorption pattern (indirectly assessed as the H-FLBZ plasma concentrations) observed after the oral administration of the FLBZ-CMC suspension or the subcutaneous injection of the Tween 80 FLBZ formulation to pigs. Overall, the work reported here indicates that FLBZ pharmacokinetic behavior can be markedly changed by the pharmaceutical formulation. Graphical abstract: Highlights: The pharmacokinetics of three different FLBZ formulations was assessed in pigs. Hydrolyzed-FLBZ was the main metabolite detected in pigs given the formulations. Traces of FLBZ and reduced-FLBZ were measured after administration of FLBZ. Oral administration of FLBZ-HPBCD solution resulted in a high systemic H-FLBZ exposure. Similar FLBZ plasma exposure was observed after parenteral FLBZ-Tween 80 and HPBCD administration.